THE PROPOSED INVESTMENT PORTFOLIO PLAN TELKOM PENSION FUND - PUSPITASARI (NIM: 29107094); Pembimbing: Prof. Dr. Ir. Sudarso Kaderi Wiryono, DEA, AMELIA
Manpower is a valuable asset for the nation and worthy to get special attention for their future especially when they entering pension period and no more productive. Pension Fund is a vehicle as well as an answer that could help them face the problem. Telkom Pension Fund (DAPENTEL) is a kind of Employer Pension Fund (DPPK) that provides the Certain Benefit Pension Program (PPMP). The program that provided by DAPENTEL is started with fund collection, fund management, and fund development activities. In managing and developing its fund, DAPENTEL performed investment in the form of portfolio. The type of investments that allowed to be managed, arranged and limited by Ministry of Finance. The more optimum the investment portfolio performance, the more guaranteed the payment of Pension Benefit for Pensioner. The condition of global recession as occured in 2008 could be happened at anytime and could decrease the investment portfolio performance of DAPENTEL so it could made DAPENTEL unable to achieve the target of investment return, Return On Investment (ROI) and the worst is unable to achieve the main objective of DAPENTEL, that is when DAPENTEL unable to fulfill its obligation to pay the pension benefit to member of DAPENTEL as it promised beforehand. This problem could be solved by performs the analysis of investment portfolio performance, the assets allocation scheme analysis, and Single Asset Volatility analysis during 2005 - 2009 to find out whether the return on investment achieved the objective (optimum return with controlled risk level) and whether the assets allocation has appropriate with Investment Guideline. Furthermore, it performed the performance evaluation of DAPENTEL's investment portfolio using the Risk Adjusted Return method which consist of Sharpe Ratio, Treynor Ratio, and Jensen's Differential Return. And then, it performed Coefficient of Variation (CV) analysis and Standard Deviaton of Investment Portfolio of DAPENTEL year 2005 up to 2009. The CV and Standard Deviation analysis could support DAPENTEL to determine the mos optimum investment portfolio for year 2010 Furthermore, based on Harry M. Markowitz's portfolio, it arranged the alternative of Investment Portfolio Design of DAPENTEL for year 2010 which is the most optimum and efficient, that is by choose the investment portfolio that have the smallest CV and Standard Deviation as well as the most optimum Average Return of several provided alternatif. From the result of the analysis, it shown that 8th Proposed Investment Portfolio is the most optimum and efficient because it has the lowest CV value (0,79%), lowest Standard Deviation (0,10%), and optimum Average of Return (12,41%). The best asset allocation is allocated in Time Deposit (1%), Deposit On Call (3%), Stock (4%), Bond (80%), Mutual Fund (1%), Government Bond of the Republic of Indonesia (10%), and Direct Investment on Share (1%). The said 8th Proposed Investment Portfolio, furthermore can be applied by DAPENTEL as decision for investment in first quarter of 2010. DAPENTEL's investment portfolio plan that is the most optimum and efficient moreover can be applied by DAPENTEL as decision on investment at first quarter of 2010. By executing the implementation steps and planning the implementation schedule, the Investment Portfolio Performance of DAPENTEL year 2010 shows the more optimum return than years before, so the main objective of DAPENTEL, which is guaranteed the payment of pension benefit, as promised in the Pension Fund Regulation (PDP) accepted by Pensioner, Widow/Widower and children up to last person, can be achieve time to time.